2020
DOI: 10.3390/app10072325
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Ship Speed Prediction towards Energy Efficient Shipping

Abstract: As oil prices continue to rise internationally, shipping costs are also increasing rapidly. In order to reduce fuel costs, an economical shipping route must be determined by accurately predicting the estimated arrival time of ships. A common method in the evaluation of ship speed involves computing the total resistance of a ship using theoretical analysis; however, using theoretical equations cannot be applied for most ships under various operating conditions. In this study, a machine learning approach was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Commonly used technologies for measuring ship speed include AIS [26], radar [27], lasers [28], and video-based speed measurements [29]. The emergence and advancement of the AIS system have provided robust technical support for acquiring ship navigation information [30].…”
Section: Techniques For Obtaining Information On Ship Speedmentioning
confidence: 99%
“…Commonly used technologies for measuring ship speed include AIS [26], radar [27], lasers [28], and video-based speed measurements [29]. The emergence and advancement of the AIS system have provided robust technical support for acquiring ship navigation information [30].…”
Section: Techniques For Obtaining Information On Ship Speedmentioning
confidence: 99%
“…A variety of studies have used AI to improve energy efficiency in maritime transport. While most of these studies focused on vessel speed optimization (Abebe et al, 2020;X. Yan, Wang, Yuan, Jiang, & Negenborn, 2018), others targeted optimizing ships' energy consumption in port (Man et al, 2020;Peng et al, 2020;R.…”
Section: Energy-efficiency Optimizationmentioning
confidence: 99%
“…ensemble methods to predict ship speed. Finally, the model optimized the actual ship route (Abebe et al, 2020).. Yan et al found the optimal speed of inland ships using the distributed parallel k-means clustering algorithm. Their proposed method contributes to lowering carbon dioxide emissions from vessels and decreasing energy consumption (Yan et al, 2018).…”
Section: Abebe Et Al Used a Decision Tree Regression Model And Fourmentioning
confidence: 99%
“…Nagalingam et al [17] presented an ensemble of extreme learning machine to estimate the longitudinal and side force coefficients as well as the yaw moment coefficient. Abebe et al [18] used various machine learning regression techniques, such as the linear regression, polynomial regression, decision tree regressor, gradient boosting regressor, extreme gradient boosting regressor, random forest regressor, and extra trees regressor techniques, to predict ship speed. The models were finally used for actual ship route optimization purposes.…”
Section: Introductionmentioning
confidence: 99%